Bowel Preparation for Colonoscopy in Nigeria - Wakama, Itekena E.; Ijah, Rex Friday Ogoronte Alderton; Madubuike, Chinyere O. (British Journal of Healthcare and Medical Research, 2022)
Background: Bowel preparation is a part of necessary preparation for all gastrointestinal endoscopic procedures. Its goal is to have a comfortable, safe, and complete examination for a possibly well motivated patient. The aim of this study was to evaluate bowel preparation carried out for lower gastrointestinal endoscopy by gastrointestinal endoscopy practitioners in Nigeria in the year 2021. Materials and Methods: A cross-sectional descriptive study was carried out among gastrointestinal endoscopy practitioners at a conference using self-administered questionnaires. Data was collected, and analysed using the Statistical Package for the Social Sciences (SPSS) version 20.0. Results: A total of eighty-two (82) respondents participated in the study. Twenty-two (26.8%) respondents asserted to carrying out ≥15 colonoscopies per month in their center of practice, and 56 (68.3%) respondents had practiced for 1-14years. Three-day bowel preparation was carried out by 22 (26.8%) respondents, and other regimens were carried out by fewer number of respondents. Bisacodyl (Dulcolax) tablets and Magnesium Sulphate (Epson salt) combination was used by 20 (24.4%) respondents. Forty (48.8%) respondents asserted to achieving ≥90% bowel preparation adequacy for colonoscopy with preferred regimen. However, twenty (24.4%) respondents have had to abandon the procedure 11 - 20% of the time due to poor bowel preparation, and 54 (65.9%) experienced procedure abandonment in less than 10% of the time. Conclusion: The practitioners of gastrointestinal endoscopy are relatively few. There is need to improve on practice by training more practitioners, and ensure uniform practice to improve outcome and patient care.